Treated wastewater effluent increases pharmaceutical concentrations and alters benthic microbial communities in streams - Lorentz, Benjamin; Rauhauser, Madeleine; Krantz, Ryan T.; Snow, Daniel D.; Kelly, John J. (Frontiers in Microbiology, 2025)
Wastewater treatment plant (WWTP) effluent can be a point source of pharmaceuticals and personal care products (PPCPs) to surface waters, and these biologically active compounds have the potential to select for resistant traits and taxa within aquatic microbial communities. The goals of this study were to determine if WWTP effluent is a point source of PPCPs to urban streams; to determine if effluent inputs affect benthic microbial community composition; and to determine if effluent inputs increase the abundance of antibiotic resistance determinants within benthic microbial communities. We collected water and sediment from three streams in the Chicago metro area: two urban streams that receive WWTP effluent and one rural stream that does not receive effluent. We quantified concentrations of a suite of 45 common PPCPs in water samples from each stream, including sites upstream and downstream of effluent inputs to the urban streams, analyzed benthic bacterial community composition, and quantified the abundance of intI1, a gene linked to antibiotic resistance. A stream receiving 80% of its flow from effluent showed higher concentrations of ten PPCPs, including several antibiotics, downstream of the effluent input, as well as decreased abundance of photosynthetic organisms and shifts in bacterial community composition, implicating effluent as the driver of these changes. We did not observe differences between upstream and downstream sites in a stream receiving only 13% of its flow from effluent. The intI1 gene did not differ in abundance within streams in response to effluent input, but intI1 abundance and PPCP concentrations were higher in the urban streams than in the rural stream. These results indicate that watershed-scale anthropogenic impacts were the driver of intI1 abundance and that non-point sources contributed to PPCP pollution.